2015
DOI: 10.1104/pp.15.01184
|View full text |Cite
|
Sign up to set email alerts
|

SHW1 Interacts with HY5 and COP1, and Promotes COP1-mediated Degradation of HY5 During Arabidopsis Seedling Development

Abstract: Arabidopsis (Arabidopsis thaliana) Short Hypocotyl in White Light1 (SHW1) encodes a Ser-Arg-Asp-rich protein that acts as a negative regulator of photomorphogenesis. SHW1 and Constitutive Photomorphogenic1 (COP1) genetically interact in an additive manner to suppress photomorphogenesis. Elongated Hypocotyl5 (HY5) is a photomorphogenesis promoting a basic leucine zipper transcription factor that is degraded by COP1 ubiquitin ligase in the darkness. Here, we report the functional interrelation of SHW1 with COP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 65 publications
(115 reference statements)
0
24
0
Order By: Relevance
“…In addition to COP1, SPA1-4 promote degradation of HY5 through COP1 (Saijo et al, 2003;Zhu et al, 2008). Another negative regulator of photomorphogenesis, SHORT HYPOCOTYL UNDER BLUE 1 (SHW1) also enhances HY5 degradation in a COP1dependent manner (Srivastava et al, 2015).…”
Section: Regulation Of Hy5 Is Dynamicmentioning
confidence: 99%
“…In addition to COP1, SPA1-4 promote degradation of HY5 through COP1 (Saijo et al, 2003;Zhu et al, 2008). Another negative regulator of photomorphogenesis, SHORT HYPOCOTYL UNDER BLUE 1 (SHW1) also enhances HY5 degradation in a COP1dependent manner (Srivastava et al, 2015).…”
Section: Regulation Of Hy5 Is Dynamicmentioning
confidence: 99%
“…Recombinant protein expression and production in E. coli were previously described (Srivastava et al, 2015). OsOTS1 (GST: OsOTS1), OsbZIP23 (OsbZIP23:His) were expressed in BL21 (DE3) cells and purified using manufacturer's guidelines for GST and histidine affinity purification tags.…”
Section: Recombinant Protein and Gst-pull Down Assaymentioning
confidence: 99%
“…It has been shown that COP1‐mediated degradation of HY5, LAF1 and HFR1 is promoted by SPA1, another negative regulator of the photomorphogenic pathway (Hoecker and Quail, ; Saijo et al ., ; Seo et al ., , ; Jang et al ., ; Yang et al ., 2005a,b; Yang and Wang, ). Recently, it has been shown that SHW1 is also involved in the stimulation of COP1‐mediated degradation of HY5 (Bhatia et al ., ; Srivastava et al ., ).…”
Section: Introductionmentioning
confidence: 97%